Ethics and gender issues in palliative care in nursing homes: an Austrian participatory research project. (June 2014) - Reitinger, Elisabeth; Heimerl, Katharina
<x xml:space="preserve">Abstract</x> Background The development of palliative care in nursing homes in German‐speaking countries has gained in importance within the past 15–20 years. Ethical and gender issues are core aspects of a palliative care culture and should therefore be better understood. Aims and objectives The aim of this study was to highlight insights regarding ethical and gender issues, based on the experiences of professionals in nursing homes. Design A 2‐year participatory action research study was performed in collaboration with three nursing homes in Austria. Methods The article focusses on 10 group discussions with interdisciplinary professional teams that were conducted to generate ethical narratives. Thematic and narrative analysis was undertaken both individually and within the interdisciplinary research team. Findings and interpretations were validated with practitioners and researchers. Findings A total of 36 narratives were collected and summarised within eight themes concerning the theoretical journey of a nursing home resident with relatives from entry into the house until death. The most burdensome ethical dilemmas are not the ones around death and dying but rather those relating to small‐scale everyday work/life issues. Sharing experiences and feelings in ethical discussions provides relief. Emotions are important facilitators of insight into ethical dilemmas. Gender issues can be observed in care situations as well as in the organisational structure of nursing homes. Conclusions Opportunities to share experiences and perspectives around ethical questions in interdisciplinary group discussions help professionals to better understand difficult issues and find appropriate ways of managing them. Implications for practice There is a need for communication structures such as facilitated ethical discussions that enable nursing home staff to reflect their everyday decisions. Expression of emotions should be encouraged in ethical decision‐making processes in nursing homes. Gender‐sensitive reflection supports the development of palliative care as organisational culture.